PENGARUH PENGGUNAAN CALF COMPRESSION TERHADAP TINGGI VERTICAL JUMP PADA PEMAIN BOLA VOLI - Mardatillah, Nicky Angen; M.Syafi’i, M.Syafi’i; Syarifah, Syarifah (Ensiklopedia of Journal, 2024)
Background: Volleyball players need a good vertical jump to perform jumping service, smash and blocking techniques. Vertical jump is a jumping movement as high as possible with leg muscle strength. Leg muscle explosiveness (power) plays an important role in vertical jump. Leg muscle strength is important in volleyball because it affects the height of the jump. Calf compression is a compression garment that can apply pressure and provide warmth to the calf to promote blood flow and muscle oscillation. Objective: Knowing whether there is an effect of using calf compression on vertical jump height in volleyball players. Methods and Subjects: This research is a type of quasi-experimental research with a one group pre-test and post-test design. The research subjects consisted of 15 members of UKM Volleyball Poltekkes Kemenkes Surakarta, who were selected using purposive sampling technique according to the predetermined inclusion and exclusion criteria. The research was conducted in January 2024. Results: Data normality was performed using the Shapiro-wilk test (<50). The results show that the pre-test data has a p value of 0.726 and the post- test data has a p value of 0.920 which indicates that the data is normally distributed. The hypothesis test used was the paired t-test with a p value of 0.001 with an mean difference of 3.67, and an increase of 0,06%. Conclusion: There is an effect of using calf compression on vertical jump height in volleyball players at UKM Volleyball Poltekkes Kemenkes Surakarta. Keywords: VolleyBall Players, Vertical Jump, Calf Compression.